O espectador doméstico e os novos canais de acesso: uma análise dos hábitos da audiência de produtos audiovisuais - Silva, Eduardo Ginesi da (2010)
The audiovisual entertainment industry has been one of the most affected by technological innovation, especially in activities as distribution of its products and provision of equipment for reproduction of music and movies. This study aims to understand the relationship among spectators and distribution channels of audiovisual products to domestic consumption. The main problem that oriented this research could be summarized as follows: What are the choices of domestic spectators to watch audiovisual products in the city of Sao Paulo? What are the common characteristics among different groups of spectators? Beyond the literature review, this research relies on two complementary phases. The first, using qualitative methods, generated variables that were applied at the second phase, based on quantitative methods. The final analysis was done on 483 respondents who said they had been used to watch movies, series or shows at home. Among the major results, it can be seen that younger consumers are more opened to using the Internet as a channel for media consumption, despite the high penetration of this tool in all age groups. It was also confirmed that the easiness of the use of new media, like memory sticks, Smartphones and Internet, together with a pro-active aptitude in consumption of this kind of products, points to emergence of a new type of viewer who has been called prosumer. This evolution of the behavior has occurred in the higher income ranges. Different medias were related to different income groups, reinforcing the impression that the price of the products has a strong impact on the selection of preferred distribution channel and, therefore, it must be well defined for the administration of the Marketing Mix. However, consumers also perceive a set of attributes uniquely for each channel, despite the fact that the audiovisual is the same for everyone. Once consumers have formed their perception about each channel, they elect their preferred one and get used to it. For industry, this choice is a fundamental factor in profitability.